Analisis Minat Belajar Dalam Pembelajaran Daring Peserta Didik Kelas V SDN 2 Pringgasela Tahun Pelajaran 2020/2021 - Warni Pitri; I Nyoman Karma; Heri Hadi Saputra (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2021)
This study aims to describe learning interest in online learning for class V students at SDN 2 Pringgasela. The approach used in this study is a qualitative descriptive approach. The subjects of this study were class V students and teachers who had implemented online learning. Methods of collecting data using a questionnaire distributed to class V students totaling 20 people, interviews with 5 students and teacher of class V taken using purposive sampling technique and user documentation. Data analysis using interactive model analysis. The results of this study indicate that the learning interest of students in online learning in each individual is generally categorized as high enough and students' interest in learning in each aspect, namely the cognitive aspect, shows that student learning interest in online learning is 33.75% which is quite high. Then on the affective aspect, it shows students' interest in learning in online learning is 39.375% which is quite high.